RISK FACTORS STUDY OF ACUTE INFECTION RESPIRATORY SYNDROME IN DISTRICT OF BANJARNEGARA - Sofiyatun, Eny; Rahayuningsih, Barnidan Vita (Universitas Ahmad Dahlan, 2014)
Background:Infection of Respiratory Syndrome is one of the cause main illness on toddler in developing country. The aim of this research was to know risk factors which influenced on Respiratory Syndrome infection, it cases in Aribaya Village, Sub-District of Pagentan, District of Banjarnegara in 2012. The risk factors included age, gender, conditions of house (included ventilations, floor, lighting, temperature and humidity), motherâs knowledge, the existence of smokers of family members, education level and occupation of mother.Method: This research used observational method with cross sectional design. 64 respondenst were participated in this research. Respondent was a person who have children under 14 years old. Random sampling technique was used to obtain data. Univariat and bivariat analyze with chi square test using SPSS 17 program was used.Result: This research revealed that there was relationship between the conditions of house ventilations (p = 0.001), the kinds of floor (p = 0.004), lighting (p = 0.001), motherâs knowledge (p = 0.001). Others factors that do not have any correlations are ages (p= 0.396), gender (p = 0.080A), the existence of smokers of family members (p = 0.355), education level of mother (p=.0134) and occupational of mother (p = 0.284).Conclusion: The recommendations were reconstructions the conditions of house according to health houses requirements. It was needed closed counseling to community from Health Center Department and local government.Â Keywords: risk factor, respiratory syndrome, Banjarnegara, toddler and mother health